Soil and water conservation effects on soil properties in the Middle Silluh Valley, northern Ethiopia - Solomon Hishe; James Lyimo; Woldeamlak Bewket (International Soil and Water Conservation Research, 2017)
Community-based Soil and Water Conservation (SWC) practices have been adopted in the Tigray region since 1991 for restoration of the degraded landscape. The effects of those conservation measures on physico-chemical properties of soil were limitedly studied. Thus, this study evaluated the effects of SWC on selected soil properties in the Middle Silluh Valley, Tigray region, Northern Ethiopia. The study considered conserved landscapes (terraced hillside, terraced farmland and exclosure area) and non-conserved landscapes (non-terraced hillside, non-terraced farmland and open grazing land) for comparison using a one-way analysis of variance (ANOVA). A total of 24 samples were collected from each landscape at a depth of 10–30 cm. The results indicated that mean bulk density (BD) was low on terraced hillside, non-terraced hillside and exclosure area. Sand and clay content were significantly different at P <0.05 for the six landscape categories. Higher mean organic matter was observed in the conserved landscape, as compared with the corresponding non-conserved landscape. Pearson's correlation between Soil Organic Matter (SOM) and clay content, SOM and Total Nitrogen (TN) showed strong positive relationships. Overall, the results show that SWC had significantly positive effects on soil's physical and chemical properties in the study area.